Upaya Peningkatan Kemampuan Pembelajaran Guru Sekolah Menengah Kejuruan Melalui Diskusi Panel Pada Kelompok Musyawarah Guru Mata Pelajaran (MGMP) Di SMK N 1 Gunung Tuleh - Zulpan S.Pd (STKIP Pesisir Selatan, 2016)
Abstract Based on observations that have researchers do To teachers at SMK N 1 Mount Tuleh, it was found that the learning ability of teachers remains low. The purpose of this study was to Improve Learning Ability teacher diSMK N 1 Mount Tuleh. This research is a school action. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of three teachers from SMK N 1 Mount Tuleh. Data were collected by using observation sheet. Data were analyzed using percentages. The results showed that the panel discussion at the Consultative Group Subject teachers can improve learning ability of teachers at SMK N 1 Mount Tuleh. This is evidenced by the increase in the learning capability of teachers from the first cycle to the second cycle. On average ability learning ability of teachers in the first cycle was 40.33 with less category and the second cycle is 83.33 with both categories. Keywords: learning ability of teachers, panel discussions, the Council Subject teachers.